2017
DOI: 10.3390/s17081788
|View full text |Cite
|
Sign up to set email alerts
|

III–V-on-Silicon Photonic Integrated Circuits for Spectroscopic Sensing in the 2–4 μm Wavelength Range

Abstract: The availability of silicon photonic integrated circuits (ICs) in the 2–4 μm wavelength range enables miniature optical sensors for trace gas and bio-molecule detection. In this paper, we review our recent work on III–V-on-silicon waveguide circuits for spectroscopic sensing in this wavelength range. We first present results on the heterogeneous integration of 2.3 μm wavelength III–V laser sources and photodetectors on silicon photonic ICs for fully integrated optical sensors. Then a compact 2 μm wavelength wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 80 publications
0
44
0
Order By: Relevance
“…Integrated optical light sources are typically based on quantum cascade or interband cascade lasers (QCL, ICL) [24,111]. The heterogeneous integration of those devices with Si-Ph platforms allows for full on-chip gas detection systems [112][113][114]. The combination of high quality active and passive components allows the use of all the discussed advanced spectroscopic methods: balanced detection, WMS and cavity enhanced spectroscopy.…”
Section: Mid-wavelength Infrared (Mir)mentioning
confidence: 99%
“…Integrated optical light sources are typically based on quantum cascade or interband cascade lasers (QCL, ICL) [24,111]. The heterogeneous integration of those devices with Si-Ph platforms allows for full on-chip gas detection systems [112][113][114]. The combination of high quality active and passive components allows the use of all the discussed advanced spectroscopic methods: balanced detection, WMS and cavity enhanced spectroscopy.…”
Section: Mid-wavelength Infrared (Mir)mentioning
confidence: 99%
“…A significant challenge however is the integration of on-chip pump source in SOI based mid-IR PICs. Although hybrid integration of near-IR sources in SOI platform is now a mature technology, there have been few demonstrations to extend this integration into mid-IR [13]. More recently, we have seen integration of QCL on Si-on-N-on-insulator (SONOI) [14].…”
Section: Introductionmentioning
confidence: 99%
“…One of the challenges that had to be addressed in this domain is to provide on-chip and low cost optical sources. It has been shown that group III-V compounds interband cascade and quantum cascade devices can provide MIR sources [6][7][8][9][10]. However, these compounds are not compatible to be efficiently grown onto the silicon platform which make the device manufacturing complicated and expensive.…”
Section: Introductionmentioning
confidence: 99%